2021
DOI: 10.1111/ijcp.14768
|View full text |Cite
|
Sign up to set email alerts
|

Identifying medication‐related readmissions: Two students using tools vs a multidisciplinary panel

Abstract: Background: Polypharmacy may result in medication-related readmissions (MRRs).Identifying MRRs is time consuming. Screening of readmissions by students could increase efficiency for healthcare professionals. Recently, two screening tools have been published: the Assessment Tool for identifying Hospital Admissions Related to Medications (AT-HARM10) tool and the Drug-Related Admission (DRA) adjudication guide. It is unknown whether pharmacy students could identify MRRs with these tools.Objective: To compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In our study, there were cases of hyperkalemia associated with a reduction in kidney function due to dehydration and events that were multifactorial (hyponatremia, fall, syncope). Coppes et al (2021) have highlighted that the tools to identify DRAs have no scale to assess the medication-relatedness of hospital admission, so some cases might be identified as drug-related, but disease progression may play a larger role. Wallerstedt et al indicated that medical doctors are more likely to attribute the hospital admission to exacerbation of disease while pharmacists tend to attribute the event to ADEs ( Wallerstedt et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there were cases of hyperkalemia associated with a reduction in kidney function due to dehydration and events that were multifactorial (hyponatremia, fall, syncope). Coppes et al (2021) have highlighted that the tools to identify DRAs have no scale to assess the medication-relatedness of hospital admission, so some cases might be identified as drug-related, but disease progression may play a larger role. Wallerstedt et al indicated that medical doctors are more likely to attribute the hospital admission to exacerbation of disease while pharmacists tend to attribute the event to ADEs ( Wallerstedt et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…AT-HARM10 has only been validated for use in older patients in Sweden, although successfully used in middle aged patients in a Swedish pilot study [24], and adult populations (age 18 years or older) in hospitals in Norway, Denmark and the Netherlands [25][26][27]. To reflect the novel use of AT-HARM10 to identify drug-related ED visits as presented in this study and to improve the tool's understandability, the tool and its instructions were revised based on feedback from other researchers that had used the tool and our own experience (Supplementary material).…”
Section: Further Researchmentioning
confidence: 99%
“…ATHARM10 was used by our research group in the MedBridge trial to assess all 2391 unplanned hospital admissions [18]. Since its publication, the tool has also been used by other research groups in Sweden, Norway, Denmark and the Netherlands [14][15][16][17]. Feedback on the tool and suggestions for improvement were requested from these researchers in an unstructured and informal way.…”
Section: Update Of At-harm10mentioning
confidence: 99%
“…AT-HARM10 has only been validated for use in older patients in Sweden, although successfully used in middle aged patients in a Swedish pilot study [22], and adult populations (age 18 years or older) in hospitals in Norway, Denmark and the Netherlands [14][15][16][17]. Further validation studies and examples the use of AT-HARM10 in other settings and populations may increase its external validity.…”
Section: Further Researchmentioning
confidence: 99%
See 1 more Smart Citation